A study of coastal and harbor channel effects on Underwater Wireless Optical Communication systems with BCH and LDPC error correction codes - Lenin Joseph; Sangeetha Anandan (International Journal of Electronics and Telecommunications)
Owing to the benefits that they offer over traditional acoustic and RF communication, including higher data rates, reduced latency, and enhanced safety, underwater wireless optical communication (UWOC) systems have gained a solid focus. However, the transmission range is rather small compared with traditional radio frequency and acoustic communications because of turbulence which makes the light beam inside the water channel fade, absorb, and scatter. In this paper, a UWOC channel model mapped with LDPC and BCH error correction techniques is used to analyze the impulse response of the channel in coastal and harbor waters. The performance of the system based on its transmission length and bit error rate (BER) is evaluated. The link distance is determined to find the maximum link distance ensuring quality UWOC. The best performance has been observed with the 4-QAM-OFDM mapped channel with LDPC codes with maximum distance of 62 m in harbor water and 161.9 m in coastal water.